Pengaruh Pengungkapan Good Corporate Governance terhadap Kinerja Keuangan Perusahaan (Studi pada Manufaktur Sektor Transportasi yang Terdaftar di Bursa Efek Indonesia Periode 2020-2022) - Gulo, Ayu Lestari; Samosir, Hendrik Elisa Sutejo; Sihombing, Halomoan S. (AKADEMIK: Jurnal Mahasiswa Humanis, 2024)
This research aims to determine the influence of Good Corporate Governance on the financial performance of companies in the transportation sector manufacturing listed on the Indonesia Stock Exchange for the 2020-2022 period. This research covers a population of 46 companies with a sample of 11 companies or 33 observations. The data used is secondary data collected using documentation data. This research data meets the requirements of classical assumption testing and hypothesis testing. The test results of this research show that the Board of Directors and Independent Commissioners variables have a negative and insignificant effect on financial performance. The suggestion given by researchers for further research is to increase the observation period in order to get a better picture and results from this research.